Sensors and Instrumentation, Volume 5 Proceedings of the 35th IMAC, A Conference and Exposition on Structural Dynamics 2017 - Wee Sit, Evro.; Walber, Chad.; Walter, Patrick; Seidlitz, Steve; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Sensors and Instrumentation, Volume 5. Proceedings of the 35th IMAC, A Conference and Exposition on Structural Dynamics, 2017, the fifth volume of ten from the Conference brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Sensors and Instrumentation, including papers on: Sensor Applications Accelerometer Design Accelerometer Calibration Sensor Technology.
Chapter1. Controlling Uncertainty in Hydraulic Drive Systems by Means of a Soft Sensor Network -- Chapter2. Non-linearity Identification of Composite Material by Scalable Impact Modal Testing -- Chapter3. Estimation of the Dynamic Focused Ultrasound Radiation Force Generated by an Ultrasonic Transducer -- Chapter4. Automated Vision-Based Loosened Bolt Detection Using the Cascade Detector -- Chapter5. Comparison of Nonlinear System Identification Methods for Free Decay Measurements with Application to MEMS Devices -- Chapter6. Vibro-acoustic Noise Analysis of a Washing Machine -- Chapter7. An Indicator Sensor Criterium for In-Situ Characterisation of Source Vibrations -- Chapter8. Experimental Study on Wireless Mobile Sensor Configurations for Output-Only Modal Identification of a Beam Testbed -- Chapter9. Trajectory Identification of a Reciprocating Drill for Geological Inspections -- Chapter10. Predicting Flight Environments with a Small-Scale Direct-Field Acoustic Test Facility -- Chapter11. Two-Year Operational Evaluation of a Consumer Electronics-Based Data Acquisition System for Equipment Monitoring.
Keywords: Mechanics, Applied; Acoustical engineering; Materials -- Analysis; Engineering Mechanics; Engineering Acoustics; Characterization and Analytical Technique